Odontogenic keratocyst involving the maxillary antrum: A case report - Choube, Amolika; Gopalakrishnan, V; Charles, NSC (Indian Journal of Case Reports, 2024)
Odontogenic keratocyst (OKC) is a benign neoplasm of the jaw with a common occurrence in the mandibular ramus area characterized by aggressive behavior and a high recurrence rate. This lesion rarely occurs in the maxilla. The aim of this report is to discuss the case of a 27-year-old male who suffered from OKC in the left maxillary antrum, which includes surgical management of the case with cyst enucleation and chemical cauterization.